A systematic review of the risk factors for suicidal ideation, suicidal attempt and completed suicide among children and adolescents in sub-Saharan Africa between 1986 and 2018: protocol for a systematic review of observational studies - Rukundo, Godfrey Zari; Kemigisha, Elizabeth; Ocan, Moses; Adriko, Wilson; Akena, Dickens Howard (Systematic Reviews, 2018)
Background: Suicide is one of the leading causes of death among children and adolescents. Most studies about the burden and risk factors for suicide have been conducted in high-income countries. However, there is a dearth in the literature about the burden and risk factors for suicide among children and adolescents in low- and middle-income countries including within Sub-Saharan Africa (SSA). There is need to summarise the available literature about the burden and risk factors for suicide among children and adolescents in SSA. In this review, we will (a) determine the overall prevalence of suicidal ideation, suicidal attempt and completed suicide among children and adolescents in SSA; (b) describe the methods (such as hanging, firearms, overdose, poisoning, drowning and burning) used for suicidal attempt, and completed suicide among children and adolescents in SSA; and (c) document the risk factors for suicidal ideation, suicidal attempt and completed suicide among children and adolescents in SSA. Methods: The review will be conducted and reported in accordance to the preferred reporting items for systematic reviews and meta-analysis (PRISMA) statement. We will include journal articles that have documented the prevalence and risk factors for suicidal ideation, suicidal attempt and completed suicide among children and adolescents aged 5–19 years in SSA. We will also include accessible grey literature about the topic. Qualitative studies will be excluded from the study since they are limited in estimating prevalence. We will search different search engines including PUBMED, EMBASE, Psych-INFO, Cochrane Library, Africa wide-information and global health using suicide, adolescents and children, SSA as the keywords. We will use a meta-analysis, should we find that there is no heterogeneity between included studies. Discussion: This protocol describes a systematic review of observational studies reporting completed suicide, suicidal ideation and suicidal attempt among children and adolescents in sub-Saharan Africa. We anticipate that once this review is complete and published, our findings will be of interest to adolescents with suicidal behavior, their families and caregivers, clinicians and other healthcare professionals, scientists and policy makers.
Keywords: Suicide; Suicidal attempt; Suicidal ideation; Suicidal behaviour; Adolescents